Drought-proofing through groundwater recharge: lessons from Chief Ministers’ initiatives in four Indian states - Verma, Shilp; Shah, Manisha (World Bank, 2019)
Indian agricultural communities are facing a crisis driven by, among other things, skewed terms of trade and farmers’ inability to deal with increasingly adverse climatic conditions. Because agriculture continues to be the primary source of livelihood for most of India’s population, governments at all levels are under pressure to find ways to help farmers. In western and peninsular India, where droughts are common, several state governments have vowed to make farming “droughtproof” through ambitious flagship programs. This case study reviews the experience of four such programs in Gujarat, Maharashtra, Telangana, and Rajasthan. Although the programs differ in approach, implementation style, and duration, all of them aim to shield farmers, particularly smallholders, from the misery imposed by droughts. Among these states, efforts in Gujarat appear to be the most mature; however, concerns regarding sustaining momentum, capacity building of communities, demand management, and establishing functional local governance remain. We use evidence gathered through field studies to draw lessons for designing effective drought mitigation strategies through improved management of groundwater resources.